Diagnosis and Management of Bladder Dysfunction in Neurologically Normal Children - Fuentes, Mirgon; Magalhães, Juliana; Barroso, Ubirajara (Frontiers in Pediatrics, 2019)
Normal bladder and urethral sphincter development as well as neural/volitional control over bladder-sphincter function are essential steps for regular lower urinary tract function These maturational sequences are clinically evident by the age of 5 years. However, in 17-22% of children, symptoms persist beyond that age, characterizing lower urinary tract dysfunction (LUTD). The clinical spectrum is wide and includes overactive bladder, voiding postponement, underactive bladder, infrequent voiding, extraordinary daytime only urinary frequency, vaginal reflux, bladder neck dysfunction and giggle incontinence. LUTD may lead to vesicoureteral reflux and recurrent urinary tract infections, increasing likelihood of renal scarring. LUTD is often associated with constipation and emotional/behavioral disorders such as anxiety, depression, aggressiveness and social isolation, making diagnosis and treatment imperative. Diagnosis of LUTD is essentially based on clinical history, investigation of bladder storage, voiding symptoms (urinary frequency, daytime incontinence, enuresis, urgency) and constipation. Dysfunctional Voiding Score System (DVSS) is a helpful tool. Physical examination focuses on the abdomen to investigate a distended bladder or palpable fecal mass, the lumbosacral spine and reflex testing. Bladder diaries are important for recording urinary frequency and water balance, while uroflowmetry is used to assess voided volume, maximum flow and curve patterns. Bladder ultrasonography to measure post-void residual urine volume and urodynamics are used as supplemental tests. Current first line treatment is urotherapy, a combination of behavioral measures to avoid postponing micturition, and a restricted diet for at least 2 months. Anticholinergics, β3 agonists and neuromodulation are alternative therapies to manage refractory overactive bladder. Cure rates, at around 40%, are considered satisfactory, with daytime symptoms improving in 32% of cases. Furthermore, children who are also constipated need treatment, preferentially with polyethylene glycol at doses of 1-1.5 g/kg in the first three days and 0.25-0.5 g/kg thereafter until the two-month period of behavioral therapy is complete. If urotherapy fails in cases of dysfunctional voiding, the next step is biofeedback to teach the child how to relax the external urethral sphincter during micturition. Success rate is around 80%. Children with underactive bladder usually need a combination of clean intermittent catheterization, alpha-blockers, biofeedback and neuromodulation; however, cure rates are uncertain.